Receptors for Respiratory Syncytial Virus Infection and Host Factors Regulating the Life Cycle of Respiratory Syncytial Virus - Feng, Ziheng; Xu, Lili; Xie, Zhengde (Frontiers in Cellular and Infection Microbiology, 2022)
Respiratory syncytial virus (RSV) is a common cause of lower respiratory tract infections and responsible for a large proportion of mortality in children and the elderly. There are no licensed vaccines available to date. Prophylaxis and therapeutic RSV-specific antibodies are limited to populations at high risk owing to high cost and uncertain clinical value. Receptors and host factors are two determinants important for virus entry and establishment of infection in vivo. The identification and understanding of viral receptors and host factors can help us to gain insight into the pathogenesis of RSV infection. Herein, we reviewed receptors and host factors that have been reported thus far. RSV could bind to CX3C chemokine receptor 1 and heparan sulfate proteoglycans via the G protein, and to nucleolin, insulin-like growth factor-1 receptor, epidermal growth factor, and intercellular adhesion molecule-1 via the F protein. Seven host restriction factors and 13 host factors essential for RSV infection were reviewed. We characterized the functions and their roles in the life cycle of RSV, trying to provide an update on the information of RSV-related receptors and host factors.